PTH-067 Yield of Endoscopic Ultrasound (EUS) in Patients with Dilated Common Bile Duct (CBD) and or Pancreatic Duct (PD) with normal Liver Function Test (LFTS) and Cross-Sectional Imaging. (4th June 2013) - Mitra, V; Nayar, M; Bonnington, S; Scott, J; Anderson, K; Charnley, R; Jaques, B; Sen, G; White, S; Manas, D; French, J; Oppong, K
Abstract : Introduction: The finding of dilated CBD or PD or both (double duct sign) on abdominal cross-sectional imaging (CT or MRI) in patients with normal LFTs frequently leads to further investigation by EUS if a clear cause is not demonstrated on imaging. There is limited literature on the yield of EUS in this setting. Methods: A retrospective review of our prospectively maintained EUS database was carried out to identify patients who underwent EUS for dilated duct(s), normal LFTs and non-diagnostic cross-sectional imaging between January 2007 and August 2011. Our aim was to evaluate the yield of EUS in this setting. Minimum follow up was for 12 months. Results: 83 patients (3% of pancreaticobiliary EUS procedures during this period) were identified. Mean age was 66.7 years (30 – 87). There was a female preponderance (73%). 40(48%) had dilated CBD only, 5(6%) had solitary PD dilatation and 38(46%) had both CBD and PD dilatation on prior imaging. EUS was concordant with prior imaging in 60(72%) patients and discordant in 23(28%) [partial agreement in 18, non-dilated ducts in 3 and different duct dilated in 2]. 16(19%) patients had a new finding on EUS [3 cbd stones, 3 cbd polyps, 4 microlithiasis, 1 ampullary adenoma, 3 chronic pancreatitis, 1 pancreatic duct adenocarcinoma (PDAC) and 1 portal vein compressing mid CBD]. Of these 11(13%) were felt to be the cause of duct dilatation. On subsequent MDT review, the PDAC was identified on the initial scan from the referring hospital. 45% (10/22) of males compared to 9.8% of (6/61) females had a new finding on EUS (p = 0.0008). Overall, more females had symptoms compared to males (p = 0.065). There was no significant association between symptoms and new finding on EUS (p = 0.24). 7(17.5%) of the isolated CBD dilatation, 3(60%) of the isolated PD dilatation and 1(2.5%) of the dilated CBD and PD had a causative diagnosis respectively. Follow up of patients with no cause of duct dilatation on EUS revealed that 18 patients (54.5%) in the dilated CBD cohort had prior cholecystectomy [one patient had peri-ampullary diverticulum and prior cholecystectomy] while 2 and 10 patients in the dilated CBD and PD cohort (n = 37) had ampullary stenosis and prior cholecystectomy respectively. Conclusion: Our study shows that EUS has a significant yield in individuals with unexplained duct dilatation and normal LFT (13% had a causative diagnosis). The yield was highest in isolated PD dilatation. A new finding was significantly more likely in men then women. EUS should ideally follow review of original cross sectional imaging by a HPB radiologist. Disclosure of Interest: None Declared.